Representasi Konflik Sosial Orde Baru dalam Novel Laut Bercerita Karya Leila S. Chudori - Luna Anastasyia Aisyah; Santi Puspasarie; Mega Fiyani (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
"The representation of the New Order conflict in the novel Laut Bercerita by Leila S. Chudori." is the working title of the study that intends to elucidate the social problems addressed in Chudori's work. Leila S. Chudori's Laut Bercerita serves as the basis for this qualitative descriptive study. Perform data analysis in accordance with the problem statement and draw conclusions from the findings. According to the study's findings, Laut Bercerita is rife with social conflicts, including those between political factions, groups, and classes, as well as amongst characters themselves. When people whose land is seized do not get justice, it leads to conflict among disadvantaged groups, as this book demonstrates. Subsequently, the novel's political battle delves into the New Order government, which leads individuals to seem to oppose the politics of that era, as well as the class struggle affecting the masses. Disagreements over the Blue Sea protagonist and the intellectuals might lead to a variety of societal problems. The government is willing to punish those who refuse to conform to the New Order, but the people who are compelled to do so have different interests. Next, the New Order era's profound societal changes that provided a snappy explanation of people's daily lives.